Rationality of Inpassing Policy for Functional Positions at West Coast Regency Secretariat - Ardi Yanto; Tabah Maryanah; Robi Cahyadi; Hertanto; M Fajar Novriansyah (PERSPEKTIF, 2023)
The adjustment/ bypassing policy is devoted to simplification of the bureaucracy which has already experienced enlargement and also burdens the government with regard to the salary payment budget. This simplification of the bureaucracy was also carried out within the Sekretariat Daerah Regency Pesisir Barat so that a rationality analysis of this policy was carried out. This descriptive research uses a qualitative approach because the study of the rationality of employee inpassing/adjustment policies within the Sekretariat Daerah Regency Pesisir Barat requires data that are not statistical or are not taken into account in the number system. This problem is analyzed using the views according to Dunn (2003) about the basis of rationality in choices. The results of this study are that the policy of inpassing/adjusting positions to functional positions is very rational in the Sekretariat Daerah Regency Pesisir Barat, this is based on the results of an analysis of the rationality aspect according to Dunn (2003). Aspects of rationality achieved in this study are aspects of economic, legal, social, and substantive rationality.